ANALISIS CADANGAN DEVISA DI INDONESIA TAHUN 1998-2019 PENDEKATAN ERROR CORRECTION MODEL - Ziyadaturrofiqoh Ziyadaturrofiqoh (Jurnal Ekonomi dan Bisnis, 2024)
Foreign exchange reserves are an important instrument in international trade that shows the weakness of the economic fundamentals so that the stability of the macro monetary and economy is a country. The condition of foreign exchange reserves must be maintained so that international transactions can take place stable. But the economic turmoil that occurs results in fluctuations in the adequacy of foreign exchange reserves in a country. The purpose of this study was to analyze the influence of exports, imports and exchange rates and foreign debt and foreign direct investment on foreign exchange reserves in Indonesia in 1998 to 2019. This study uses the error correction model method to analyze the effect of independent variables against equipped with Stationer test, long-term estimation test and cointegration test and classical assumption test. Based on the results of the study, it can be seen that in the long term which influences foreign exchange reserves is the variables of ekspor, import and foreign debt while in the short term which has an influence is an export variable, imports, exchange rates and foreign debt. The results of the study are expected to provide solutions to the government and other institutions as monetary authorities in taking steps to determine policies related to foreign exchange reserves.